Fish guild structure along a longitudinally-determined ecological zonation of Teesta, an eastern Himalayan river in West Bengal, India - M. Chakrabarty; S. Homechaudhuri (Arxius de Miscel-lània Zoològica)
The Eastern Himalaya Biodiversity Hotspot contains exceptional freshwater biodiversity and ecosystems that are of vital importance to local and regional livelihoods, but these are under threat from the developmental and anthropogenic pressures arising from the 62 million people living in the area. Therefore, monitoring the riverine health and considering future conservation approach, the study of fish biodiversity plays a significant role in this region. The River Teesta in the Brahmaputra basin in India forms one of the major rivers in the Eastern Himalayas. In the present investigation, we studied ecological fish guilds as they can enhance the usefulness of fish zonation concepts and serve as tools to assess and manage the ecological integrity of large rivers. We classified fish species according to their water flow preference and spawning substrate preference. Ten spawning habitats were identified, occurring in three water flow guilds. The most widely preferred habitat in upstream zones was lithophils while in lower stretches it was lithopleagophils. On applying predictions of the River Continuum Concept, our results indicated the presence of a zonation pattern based on fish species assemblage and their ecological attributes along the longitudinal stretch of the Teesta River in west Bengal. Along the longitudinal stretch of the river, species richness increased downstream, with maximum richness in the mid-reaches. However, species richness decreased further downstream. The number of ecological guilds also increased downstream, and there were clear shifts in the structure of the guilds.